Solitons in isotropic antiferromagnets: beyond a sigma model - Galkina, E.G.; Galkin, A.Yu.; Ivanov, B.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
Isotropic antiferromagnets shows a reach variety of magnetic solitons with nontrivial static and dynamicproperties. One-dimensional soliton elementary excitations have a periodic dispersion law. For two-dimensionalcase, planar antiferromagnetic vortices having nonsingular macroscopic core with the saturated magneticmoment are present. The dynamic properties of these planar antiferromagnetic vorteces are characterizedby presence of a gyroforce.